A phase 1 trial of xentuzumab, an IGF‐neutralizing antibody, in Japanese patients with advanced solid tumors. Issue 3 (13th January 2022) - Doi, Toshihiko; Kuboki, Yasutoshi; Naito, Yoichi; Ishida, Masahiro; Tanaka, Tetsuya; Takeuchi, Yoshito
Abstract: Xentuzumab is an insulin‐like growth factor (IGF) ligand‐neutralizing antibody. This phase 1 trial assessed xentuzumab in Japanese patients with solid tumors. Patients aged ≥20 y old with solid tumors that were refractory or not amenable to standard therapy were enrolled. Patients received xentuzumab intravenously at a starting dose of 750 mg/wk. Dose escalation used a 3 + 3 design with dose de‐escalation. The primary endpoint was to determine the maximum tolerated dose (MTD) of xentuzumab. Safety, pharmacokinetics, pharmacodynamics, and anti‐tumor activity were also assessed. Fifteen patients received xentuzumab in the dose escalation part (750 mg/wk [n = 6]; 1000 mg/wk [n = 3]; 1400 mg/wk [n = 6]). There were no dose‐limiting toxicities at any dose; the MTD of xentuzumab was not reached. Xentuzumab 1000 mg/wk was recommended as the relevant biological dose. Six further patients received xentuzumab 1000 mg/wk in an expansion cohort. Of 21 patients, 13 (61.9%) experienced a drug‐related adverse event, most commonly fatigue (23.8%), neutropenia (19.0%), diarrhea, nausea, white blood cell count decrease, and muscle spasms (14.3% each). No relevant deviations from dose linearity of xentuzumab exposure were observed during dose escalation. Total IGF‐1 and IGF‐2 levels increased and bioactive IGF levels decreased from baseline to 24 h after the first infusion in cycle 1. Partial response was observed in 2 (9.5%) patients with desmoid‐type fibromatosis. Disease control was achieved in 6 (28.6%) patients (median duration 42.4 mo). Xentuzumab monotherapy was well tolerated in Japanese patients and showed evidence of anti‐tumor activity. This study was registered with www.clinicaltrials.gov (NCT02145741). Abstract : This phase 1 study assessed the safety and anti‐tumor activity of xentuzumab in 21 Japanese patients with solid tumors. Treatment was generally well tolerated with no significant changes in blood glucose levels and no drug‐related grade ≥3 adverse events. Two patients (9.5%) had a partial response and disease control was achieved in a total of 6 patients (28.6%); both patients with partial responses and 2 patients with stable disease had sarcomas.